How the Use of Fees, Fines and Bail Have Been Used to Criminalize Poverty: Can Reforms Help Put the Genie Back in the Bottle? - Thomas Allan Heller (LeXonomica, 2024)
The rallying cry of many American politicians is Law and Order. This tactic wins votes. As a result of its Wars on Crime, Drugs, and the Impoverished, America has the highest rate of incarceration in the world.  This article explores how, over the past few decades, politicians have charged criminal defendants every imaginable fee and fine as they wind their way through the criminal justice system in order to fund the massive prison complex that the politicians do not want to tax Americans for. These tactics have criminalized poverty, as they disproportionately impact the most marginalized in American society. These abusive and unfair tactics have drawn scrutiny from policymakers in recent years, including the American Bar Association, which adopted stringent guidelines to help inform policymakers of this critical problem in an effort to reign in the abusive use of fees and fines. The paper discusses recent reforms, many at the urging of the Department of Justice, Office for Access to Justice, in conjunction with the ABA.  It discusses the main Supreme Court cases that considered the Excessive Fines Clause of the Eighth Amendment. PovzetekŠtevilni ameriški politiki se sklicujejo na zakon in red. Ta taktika prinaša glasove. Zaradi vojn proti kriminalu, drogam in obubožanim ima Amerika najvišji delež zapornikov na svetu.  Ta članek raziskuje, kako so politiki v zadnjih nekaj desetletjih obdolžencem kaznivih dejanj zaračunavali vse možne pristojbine in globe, ko so se prebijali skozi kazenskopravni sistem, da bi financirali ogromen zaporniški kompleks, za katerega politiki nočejo plačevati davkov Američanom. Ta taktika je kriminalizirala revščino, saj nesorazmerno močno vpliva na najbolj marginalizirane v ameriški družbi. Te zlorabljajoče in nepoštene taktike so bile v zadnjih letih deležne pozornosti oblikovalcev politike, vključno z Ameriško odvetniško zbornico, ki je sprejela stroge smernice za pomoč pri obveščanju oblikovalcev politike o tem kritičnem problemu, da bi omejili zlorabljajočo uporabo pristojbin in glob. V dokumentu so obravnavane nedavne reforme, ki so bile številne izvedene na pobudo Urada za dostop do pravnega varstva pri Ministrstvu za pravosodje v sodelovanju z združenjem ABA.  Obravnava glavne primere Vrhovnega sodišča, ki so obravnavali klavzulo o pretiranih globah iz osme spremembe.